Sustainable Homestay Marketing Strategy: Triple Bottom Line Implementation for Post-Pandemic Economic Recovery in Pulesari Tourism Village - Pratama, Oktarini; Sari, Rini Eka; Kuntari, Erlina Ndaru; Nilzam Aly, M (Jurnal pariwisata terapan (Online), 2024)
The development of tourism villages is an important issue in implementing sustainable tourism principles related to the triple bottom line concept. Pulesari Village is expected to become a tourist village that is able to integrate economic (profit), social (people), and environmental (planet) interests in managing its homestay business. The purpose of this research is to understand the homestay marketing model carried out by the Pulesari Tourism Village Manager in relation to the triple bottom line concept. This research uses data collection techniques through non-participatory observation, in depth interviews, and documentation. The results of this study found that the community owns assets in the form of homestays and is managed professionally together with an institution formed by the village. A percentage profit-sharing system is used as an instrument for sharing income from homestay management. However, efforts to maintain environmental quality are still not the main promotional material because there are still weaknesses, especially in waste management. The community as part of the subject of economic activity in Pulesari Tourism Village needs to be further involved in the process of homestay management and marketing while balancing economic, social and environmental interests.